Uji Validitas Sebagai Penentuan Kualitas Butir Soal Pilihan Ganda "Pacu Kimia" FMIPAK Unima - Waworuntu, Freetje; Tuerah, Jeanne M; Tengker, Soenandar M; Saiya, Abdon; Paat, Vlagia; Rumengan, Stefan (Oxygenius: Journal Of Chemistry Education, 2024)
The purpose of this research is to determine the quality of multiple-choice items in the "Chemistry Boost" test from FMIPAK Unima, based on responses from 80 high school students answering 40 items. The validity test used a combination of Discrimination Index (DI) and Difficulty Level (DL). DI has 6 categories: Very Good, Good Enough, Marginal, Poor Discrimination, Negative, while DL consists of 6 categories: Discarded, Very Easy, Easy, Maintained, Very Difficult, and Reviewed for deficiencies or taught. The results obtained are 23 valid items, or 57.5%. Based on the results, the cognitive processes of Anderson's revised Bloom Taxonomy were determined, with valid items in C1, C2, C3, C4, C5, and C6 being 2, 2, 12, 6, 0, respectively. Items categorized as Higher Order Thinking Skills (HOTS) are in C4 and C5, totaling 18 items. Valid chemistry topics include Acid-Base, Atomic Structure, Stoichiometry, and Reaction Rates. Topics less understood by participants include Compounds and Chemical Formulas, Solubility, Chemical Equilibrium, Ionization Energy, Redox, Electrochemistry, and Hydrocarbons.